Passion for sport as a mediator between the basic psychological needs and life satisfaction of athletes with disabilities - Rodrigues, Filipe (2023)
The present study examined the potential impact of basic psychological needs and passion for the practiced sport on the life satisfaction of athletes with disabilities. A mediation model was tested, hypothesizing that autonomy, competence, and relatedness are associated with athletes' life satisfaction through their passion (harmonious and obsessive) for the sport. One hundred thirty-one athletes participated in this study, ranging in age from 15 to 59 years (M = 27.78; SD = 9.31). Athletes completed questionnaires regarding their satisfaction of basic psychological needs in sports, their passion for the sport, and overall life satisfaction. Perceptions of competence and relatedness were associated with harmonious passion (β = 0.37, p < 0.01; β = 0.21, p < 0.05, respectively), while perceptions of autonomy were linked to obsessive passion (β = 0.39, p < 0.05). Furthermore, harmonious passion was linked to life satisfaction (β = 0.40, p < 0.01), and only the indirect effect of competence on life satisfaction through harmonious passion was significant. The results suggest that autonomy satisfaction does not necessarily translate into higher levels of harmonious passion. However, competence and relationships play a significant role in the life satisfaction of athletes who have a harmonious passion for their sport.